Exploring Cervical Cancer Screening Uptake among Women in the United States: Impact of Social Determinants of Health and Psychosocial Determinants - Matthew Asare; Eyram Owusu-Sekyere; Anjelica Elizondo; Gabriel A. Benavidez (Behavioral Sciences)
Several non-medical factors, such as income, education, and access to care, directly or indirectly affect adherence to cancer screening guidelines. We examined the impact of social determinants of health (SDOH) and psychosocial factors on screening behavior in a nationally representative sample of women in the US. A retrospective population-level cross-sectional sample was extracted from the 2022 Health Information National Trends Survey. The dependent variables were the interest in cervical cancer screening and the screening behavior. The independent variables included SDOH and psychosocial factors. Descriptive statistics were calculated for demographics and covariates, and population-based estimates with 95% confidence intervals (CI) were produced for Pap testing behaviors. Logistic regression models assessed differences in Pap testing based on SDOH and psychosocial factors, adjusting for covariates. The study included 2224 women with a mean age of 46.96. Results showed that 90% of women were interested in cervical cancer screening, with an 80% screening rate. Screening rates varied by age and rurality. SDOH and psychosocial factors influenced both interest and actual screening, with 3% and 1% impacts, respectively. These findings suggest that SDOH and psychosocial factors are associated with cervical cancer screening uptake, highlighting the need for policies to address these disparities. Policies must be directed at bridging the gap created by these SDOHs. Public health professionals and researchers can design interventions using the SDOH and psychosocial frameworks to increase cervical cancer screening uptake.